Кількісні морфологічні ознаки та мінливість вегетативних і генеративних органів бузини чорної (Sambucus nigra L.) у Лісостепу України - Kolisnyk, L.M.; Klymenko, S.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Quantitative morphological signs of vegetative and generative organs of an elderberry (Sambucus nigra L.) forms, selected in natural populations in Ukraine, are investigated. Variability is shown, the range of variations of signs for an estimation of selection value perspective forms is defined.